Effects of Nitrate-Rich Beetroot Supplements on Anaero-bic Power, Speed-Characteristic Performance, and Explosive Leg Strength on Football Players - AL-Nedawi, Rand; AL-Nedawi, Ola; Jubair, Raghda; Al-Mu’min, Hussam (Journal of Posthumanism, 2025)
Athletic performance is influenced by physiological and nutritional factors, with dietary nitrate supplementation emerging as a potential er-gogenic aid. Beetroot, rich in nitrates, has been shown to enhance oxygen utilization and muscular efficiency. However, its effects on anaerobic power, speed-characteristic perfor-mance, and explosive leg strength in football players remain unclear. This study investi-gates the impact of beetroot supplementation on these key performance variables. Meth-ods: A controlled experimental study was conducted with 20 youth football players from Al-Sinaa Club (aged 17-19 years), randomly assigned into an experimental group (n = 10) consuming 500 ml of nitrate-rich beetroot juice daily for eight weeks and a control group (n = 10) maintaining their regular diet. Performance assessments included the Wingate Anaerobic Test for anaerobic power, a 30-meter sprint test for speed, and vertical jump and three-hop tests for explosive strength. Data were analyzed using SPSS software. Re-sults: The experimental group exhibited significant improvements compared to the con-trol group. Peak anaerobic power increased significantly (p = 0.000), and the time to reach peak anaerobic power decreased (p = 0.000). Maximum sprint speed improved, with sprint times decreasing (p = 0.000). Speed-specific strength in both legs and explosive leg strength also showed significant enhancements (p < 0.05). Conclusions: Nitrate-rich beet-root supplementation effectively enhances anaerobic power, sprint performance, and ex-plosive strength in football players. These findings support its use as a natural ergogenic aid for optimizing high-intensity sports performance. Future research should explore long-term effects and dosage optimization.